2014
DOI: 10.3892/mmr.2014.2038
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the gene expression levels of microRNAs in the rat hippocampus by sevoflurane and propofol anesthesia

Abstract: Abstract. General anesthesia is commonly used in the surgical arena, but little is known regarding its influence at the genomic and molecular levels. MicroRNAs (miRNAs) belong to a new class of non-coding RNA molecules which influence cell biology. In the present study, it was hypothesized that miRNAs alter gene expression levels under general anesthesia. The aim was to compare the miRNA expression profiles in the rat hippocampus in response to anesthesia with representative volatile (sevoflurane) and intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…The reasons underlying the difference between their results and those of the present study remain to be elucidated. However, one notable difference is that Goto et al (14) conducted experiments on 6-week-old male Wistar rats, whereas 7-day-old Sprague-Dawley rats were employed in the current study. Previous studies have demonstrated that ketamine leads to neuroapoptosis in the developing brain (26), and that miR-34a negatively regulates ketamine-induced apoptosis in the hippocampus (15).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The reasons underlying the difference between their results and those of the present study remain to be elucidated. However, one notable difference is that Goto et al (14) conducted experiments on 6-week-old male Wistar rats, whereas 7-day-old Sprague-Dawley rats were employed in the current study. Previous studies have demonstrated that ketamine leads to neuroapoptosis in the developing brain (26), and that miR-34a negatively regulates ketamine-induced apoptosis in the hippocampus (15).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, miR34c was selected for further investigation. Notably, Goto et al (14) reported a contrasting result. In this previous study, 4 miRNAs were observed to be significantly increased, while 12 miRNAs were significantly reduced in the rat hippocampus following sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar dose was also used in previous studies (40,41). None of these pups appeared to undergo hypoxemia or hypocapnia during the sevoflurane exposure for 4 h, as verified by their arterial blood analysis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA microchip technology provides for simultaneous detection of the global expression of several hundred miRNAs in a single sample, and it has been previously used to characterize the miRNA transcriptomic signatures of anesthetic agents in the liver (Ishikawa et al, 2012) and hippocampus (Goto et al, 2014). Here, we used miRNA microchips and quantitative real-time polymerase chain reaction (qRT-PCR) to characterize the effect of lowand high-dosage propofol on miRNA expression patterns in primary cultures of hippocampal astrocytes isolated from immature rats.…”
mentioning
confidence: 99%